MATERNAL MORTALITY IN CEARÁ-BRAZIL (1998 -2002):RETROSPECTIVE STUDY - Escolástica Rejane Ferreira Moura; Maria Socorro Ramos da Ponte; Raimunda Magalhães da Silva; Marcos Venícios de Oliveira Lopes (Universidade Federal do Paraná, 2007)
The study aimed to analyze maternal deaths recorded in Ceará/ Brazil from 1998 to 2002 (n = 621). The data weresupplied by Epidemics Surveillance of Ceará Health Bureau. Xv²(x squared) test or Maximum Ratio Probability for tables RxS wasused to analyze the association among the categorized variables. Most deceased women were between 20 and 34 years, low income,gestational interval larger than two years and delivery up to four children. Consultation number analysis was harmed by informationshortage and for the fact that gestational age was not analyzed at the time of the death. Deaths mostly happened at the hospital, assistedby doctors and obstetricians. Maternal death should be observed under care delivery quality on prenatal, childbirth and after-childbirth,so that technical accuracy and care-rendered commitment with respective recording be set up.